2018
DOI: 10.1029/2018gl079033
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Internal Variability and External Forcing to the Recent Pacific Decadal Variations

Abstract: There is substantial uncertainty in the relative contributions of internal variability and external forcing to the recent Pacific decadal variability, especially regarding their linkage with the Interdecadal Pacific Oscillation. By analyzing observations and large ensembles of coupled climate model simulations, here we show that observed Pacific decadal variations since 1920 resulted primarily from internal variability, although greenhouse gas (GHG) and other external forcing did modulate decadal variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 51 publications
1
58
0
Order By: Relevance
“…Note that ̃ decreases upwards on the vertical axis, in order that the effective climate sensitivity increases upwards of climate change to forcing agents (e.g. Jones et al 2013;Hua et al 2018).…”
Section: Time-variation Of Climate Feedback In the Historical Experimentsmentioning
confidence: 99%
“…Note that ̃ decreases upwards on the vertical axis, in order that the effective climate sensitivity increases upwards of climate change to forcing agents (e.g. Jones et al 2013;Hua et al 2018).…”
Section: Time-variation Of Climate Feedback In the Historical Experimentsmentioning
confidence: 99%
“…Previous studies show many different ways to calculate the index representing the PDO/IPO: for example, the EOF method (Mantua and Hare 2002) and the difference of SST anomalies between regions of the Pacific (Henley et al 2015;Salzmann and Cherian 2015), showing an overall similarity in featuring the decadal-tomultidecadal variability of Pacific SST in observations after 1920 (Hua et al 2018). Thus, for easier calculation and for direct comparison between observations and model simulations and comparison between ensemble members, we use the latter method to define the IPO index without applying EOF analysis, similar to Salzmann and Cherian (2015).…”
Section: ) Ipo Definitionmentioning
confidence: 99%
“…Changes in land use and land cover have also been proposed as another contributor: Local evapotranspiration, a source of atmospheric moisture, has decreased as a consequence of deforestation (Paul et al 2016;Chou et al 2018). In addition to the above anthropogenic forcings, a negative-to-positive phase transition from the 1950s to the 1990s of the Pacific decadal oscillation (PDO)/interdecadal Pacific oscillation (IPO), whose recent cycles result mainly from internal variability (Dong et al 2014;Hua et al 2018), also helps to explain the total drying trend over India during this period, as highlighted by Salzmann and Cherian (2015). Using the multimodel ensemble from phase 5 of the Coupled Model Intercomparison Project (CMIP5), the NCI drying trend associated with the PDO/IPO was comparable to that caused by anthropogenic aerosols derived from the single-forcing experiments during the period 1950-99 (Salzmann et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Pacific decadal Oscillation (PDO) (Mantua et al ., ) or the Inter‐decadal Pacific Oscillation (IPO) (Power et al ., ) is the dominant mode of decadal to multi‐decadal sea surface temperature (SST) variability in the Pacific Ocean that broadly resembles the SST anomaly pattern of ENSO but with subtle differences (Zhang et al ., ; Dong et al ., ). Many studies have found that this internal mode could exert large decadal/inter‐decadal modulation effects on regional and global temperature and precipitation (e.g., Zhang et al ., ; Reason and Rouault, ; Krishnan and Sugi, ; Meehl and Hu, ; Dai, ; Dong and Dai, ; Newman et al ., ; Hua et al ., ). Since the IPO/PDO mode provides a major source of decadal predictability, understanding the physical connections between the IPO/PDO and the associated regional climate variations is critically important.…”
Section: Introductionmentioning
confidence: 97%